2020
DOI: 10.3389/fpsyt.2020.590134
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Motor, Cognitive, and Behavioral Symptoms in Parkinson's Disease and Mild Cognitive Impairment During the COVID-19 Lockdown

Abstract: Objective: The effects of the COVID-19 lockdown on subjects with prodromal phases of dementia are unknown. The aim of this study was to evaluate the motor, cognitive, and behavioral changes during the COVID-19 lockdown in Italy in patients with Parkinson's disease (PD) with and without mild cognitive impairment (PD-MCI and PD-NC) and in patients with MCI not associated with PD (MCInoPD).Methods: A total of 34 patients with PD-NC, 31 PD-MCI, and 31 MCInoPD and their caregivers were interviewed 10 weeks after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 36 publications
1
65
1
2
Order By: Relevance
“…This rapid review also found a large proportion of people with dementia experiencing decline in their cognitive abilities during the lockdown [ 11 , 20 , 21 , 23 , [28] , [29] , [30] , 32 ] The majority of studies report cognitive decline in more than 50% of the sample examined. However, one study reported figures of 41–45% [21] and another 12% [22] . While people with dementia deteriorate gradually over time the decline reported by these studies occurred in an unusual short window of time (3,4 months).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This rapid review also found a large proportion of people with dementia experiencing decline in their cognitive abilities during the lockdown [ 11 , 20 , 21 , 23 , [28] , [29] , [30] , 32 ] The majority of studies report cognitive decline in more than 50% of the sample examined. However, one study reported figures of 41–45% [21] and another 12% [22] . While people with dementia deteriorate gradually over time the decline reported by these studies occurred in an unusual short window of time (3,4 months).…”
Section: Discussionmentioning
confidence: 94%
“… November 2019 and June 2020 (3 months after home confinement) 80% 44% NPI: 5.72 (pre-confinement) 10.25, (post-confinement) * Barthel Index: (pre-confinement) 92.92-(post-confinement) 88.33* 11% (type of change not reported) 7/9 § Studies with one time point data collection (during or after lockdown) Study Country Setting N† Measure used Time of data collection Decline in Cognition Appearance or worsening of behavioural/psychological symptoms ADL Increase/addition pharmacological therapy Quality score (max 8) Baschi et al. [21] Italy Outpatient clinic. PD-MCI: 31 MCI: 31 Semi-structured questionnaire NPI 2 months before lockdown and immediately after end of lockdown 45% (PD-MCI) 41% (MCI) Worsening of existing symptoms: 42% (PD-MCI) 38% (MCI) New symptoms: 42% (PD-MCI), 22% (MCI) Number of IADL lost (1.6 ± 1.8 (PD-MCI) Number of IADL lost 0.8 ± 1.2 (MCI) NR 7 Palermo et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies show that patients with pre-existing NCDs have found it difficult to maintain a healthy lifestyle during the COVID-19 pandemic and associated lockdown measures introduced by countries 227 . Patients with coronary heart disease [228][229][230][231][232] , neurological disorders 233,234 , diabetes 235,236 and cancer 237,238 have had to compromise on their physical activity routine, dietary patterns, and social connectedness in particular 227,236,239,240 as did families with children who had chronic respiratory diseases 193,241 . Poor glycemic control in diabetics due to altered lifestyle was reported in many studies [242][243][244][245][246][247][248] , while one study in India reported an improvement in the glycemic status of patients with type II diabetes mellitus 249 .…”
Section: Lifestyle Factors In Patients With Pre-existing Ncdsmentioning
confidence: 99%
“…This point is of interest for the study of ageism. Nevertheless, one should not forget that social isolation is also associated with increased risks of cognitive impairment, increasing the risk of developing neurocognitive disorders or accelerates the progression of pre-existing diseases (Baschi et al, 2020 ).…”
Section: Risks To Older People In Covid-19 Responsementioning
confidence: 99%